Determining proper irrigation method and schedule in maize production for semi-arid environment in Nigeria - Bashir, Ali Umar (2017)
Water scarcity due to the impact of climate change and the increasing global demand for water from many sectors including agriculture, has become a global concern especially in semi-arid regions where irrigation is the only alternative for crop production to meet the demand for food for the rapidly growing population. Maize production in the semi-arid region of Nigeria relies widely on irrigation. This is due to the extremely irregular rainfall, to the extent that the amount and distribution in space and time had not been ideal to optimally support crop production adequately. Farmers in the region use furrow irrigation method and fixed irrigation interval schedule for maize production. The irrigation method and schedule used by the farmers has become unsustainable due to low yield, low water use efficiency, low quality of maize kernels and low net farm income. Thus, there is a growing gap between the demand for maize and its production to meet the food requirement for the growing population in the region. The aim of this study was to determine the proper irrigation method and schedule in maize production for semi-arid environmental of Nigeria. Two field experiments were conducted in the 2014 and 2015 seasons at the Teaching and Research Farm of Ramat Polytechnic Maiduguri, Borno State which is located in the semi-arid region of Northern Nigeria. The experiments consisted of a factorial combination of irrigation methods and scheduling methods laid in a randomized complete block design that resulted in nine (9) treatments. Irrigation methods were at 3 levels namely; drip, sprinkler and furrow irrigation methods. Irrigation scheduling methods were also at three levels namely fixed irrigation interval (7days), soil moisture based schedule using tensiometer at trigger level of 30 cbar and climate based schedule based on the ratio of irrigation amount to cumulative pan evaporation of 1 (1.0 IW/CPE). The treatments were randomly assigned to plots and replicated 3 times. A total of 27 experimental plots were used for the study. Samples of water were taken from the source of water (tube wells) used for the irrigation of the maize crop and analyzed to ascertain its suitability or otherwise for irrigation. The samples were analysed for physicochemical properties using the procedures recommended in the standard methods for the examination of water and waste water and the values of total dissolved solids, sodium adsorption ratio, magnesium adsorption ratio, residual sodium carbonate and Kelly ratio were calculated. Growth, yield and yield parameters that were recorded during the crop growth and development were subjected to Analysis of Variance (ANOVA) to determine the effect of irrigation methods and irrigation schedules on the growth, yield and yield components of maize using Statistical Analysis System (SAS 9.4) software. Duncan multiple range test (DMRT) at P 0.05 was used to compare significantly different means and their interactions. Correlation analysis was performed to determine the relationship between growth and yield parameters with yield. The crop water use and irrigation water use efficiencies, maize kernel quality, the performance of irrigation systems used in terms of uniformity of water distribution, water savings and their irrigation efficiencies were evaluated. The economic viability of maize production under the different irrigation and scheduling methods were determined. The result of the water quality analysis revealed that the source of water in the study area is free from salinity, permeability and toxicity problems and is suitable for irrigation usage. . The result of the study revealed that the growth, yield and yield parameters were significantly affected by irrigation methods and schedules in both growing seasons with better performance from drip compared to sprinkler and furrow irrigation methods. The result also shows that maize performed better under sprinkler compared to furrow irrigation method. The result further revealed that, plots scheduled using tensiometer and the ratio of irrigation amount to cumulative pan evaporation methods that resulted in 4days irrigation interval performed better compared to the fixed interval (7 days). The highest values of crop water use and irrigation water use efficiencies of 0.92 and 0.73 kg/m3 respectively were obtained from drip irrigated plots scheduled with tensiometer compared to 0.73 and 0.56 kg/m3 for sprinkler and 0.66 and 0.41 kg/m3 for furrow. The result further showed that the use of drip irrigation method has resulted in water savings of 17.31% and 31.75% when compared with sprinkler and furrow irrigation methods respectively. The uniformity of water distribution was higher in drip irrigation method with emission uniformity of 91.2% compared to sprinkler with a coefficient of uniformity of 75% and furrow with distribution uniformity of 75%.The irrigation efficiencies of the drip, sprinkler and furrow irrigation methods used were 80%, 76% and 64% respectively. The result on the effect of irrigation methods and schedules on the quality of maize showed that maize crop irrigated using the drip irrigation method had the highest contents of carbohydrate, ash and fibre of 73.04%, 2.40% and 2.56% respectively. While plots scheduled using tensiometer and the ratio of irrigation amount to cumulative pan evaporation (IW/CPE) which resulted in 4 days irrigation interval gave the highest ash, fibre and carbohydrate contents 2.08%, 2.11% and 71.33% respectively compared to the fixed irrigation interval of 7 days The economic analysis result revealed that, the combination of drip irrigation and tensiometer schedule had the highest net farm income and benefit cost ratio of $695.2 and 3.20 respectively compared to $460.8 and 1.99 for sprinkler and $545.8 and 2.84 for furrow irrigation method. The findings of this study revealed that the combination of gravity drip irrigation method and soil moisture and climate based schedules that resulted in 4 days irrigation interval is the most economically viable alternative in maize production for the semi-arid region environment of Nigeria for improved yield, higher water savings and water use efficiency as well as higher maize kernels quality. The study established infiltration models which are useful in the design of irrigation and drainage systems; soil and water characteristics models for scheduling irrigation and production model for describing the relationship between yield and actual evapotranspiration for making sound management decisions by farmers for optimum production. Further study is recommended on the viability of pressurized drip irrigation on field-scale in terms of yield improvement, water use efficiency, water savings and profitability of maize production.